Analysis and Design of Robust Positivity and Stability for Continuous-Time Linear Uncertain Systems - Kuo-Liang Yen; Kuo-Shong Wang; Yau-Tarng Juang (Journal of Applied Mathematics)
This paper deals with the analysis and design of positivity and stability of linear continuous conic systems. First, two robustness analysis theorems are proposed for the systems with state-feedback. Second, the state-feedback stabilization problem is solved by using linear programming (LP). Numerical examples are given for illustration. Finally, the conclusions are made.